PENINGKATAN KETERAMPILAN BERBICARA MENGGGUNAKAN METODE DEBAT - Diana Puspa; Dadang Kurnia; Rini Sri Indriani (STKIP Subang, 2023)
This research was carried out using a Case Study Qualitative Research Approach. The purpose of this study is to improve speaking skills using the debate method. The subjects of this study were high-class students, namely V E State Elementary School Cileungsi 06. Data collection in this study was carried out by conducting observations, interviews, and also collecting data and documentation to support the research. The results of the study can be concluded that the debate method can improve the speaking skills of fifth grade students at Cileungsi 06 State Elementary School, Bogor Regency. The conclusions can be drawn namely: an increase in speaking skills using the debate method which can be seen from the six subjects through the percentage results of the debate assessment of the final results of the subject. get their respective percentages, namely the subject with the initials ''AL'' with a percentage result of 61.53%, then the subject with the initials ''AR'' with a percentage result of 62.5%, the subject with the initials ''DZ'' with a percentage result of 54.16% , the subject has the initials ''DA'' with a percentage of 75%, the subject has the initials ''K'' with a percentage of 50%, and the subject has the initials ''R'' with a percentage of 75%.